ANALISIS KADAR VITAMIN A WORTEL (Daucus carrota) LOKAL DAN IMPOR YANG BEREDAR DI KOTA MAKASSAR - Alang, Hasria (STKIP Pembangunan Indonesia Makassar, 2015)
The research about â€œThe Analysis of different in the level of Vitamin A from local and import Carrots (Daucus carrota) that circulating in the city of Makassar has been done.Â This research was an experimental study conducted and held in February at Large Hall in Sout Sulawesi Propincy. Sampling was carried out two take places, local Carrots from some tradisional markets and import Carrots from supermarkets in Makassar. The result of the research when analyzed by spectrofotometry UV-VIS at the maximum wavelength indicates that the average levels of the Vitamin A in the local Carrots is 357,5 ug/g dan import carrots is 1496,4 ug/g